Total ankle arthroplasty and ankle arthrodesis affect the biomechanics of the inner foot differently - Wang, Yan (Sci Rep, 2019)
Ankle arthrodesis and total ankle arthroplasty are the two primary surgeries for treatment of end-stage degenerative ankle arthritis. The biomechanical effects of them on the inner foot are insufficient to identify which is superior. This study compared biomechanical parameters among a foot treated by ankle arthrodesis, a foot treated by total ankle arthroplasty, and an intact foot using computational analysis. Validated finite element models of the three feet were developed and used to simulate the stance phase of gait. The results showed total ankle arthroplasty provides a more stable plantar pressure distribution than ankle arthrodesis. The highest contact pressure, 3.17 MPa, occurred in the medial cuneonavicular joint in the total ankle arthroplasty foot. Neither of the surgeries resulted in contact pressure increase in the subtalar joint. The peak stress in the metatarsal bones was increased in both surgical models, especially the second and third metatarsals. This study enables us to get visual to the biomechanics inside of an intact foot, and feet treated by total ankle arthroplasty and ankle arthrodesis during walking.